A primer on critical thinking and business ethics. volume 1 : recent conceptualizations of critical thinking - Mascarenhas, Oswald A. J.; Thakur, Munish; Kumar, Payal, 1966- (Emerald Publishing Limited, 2023)
A Primer on Critical Thinking and Business Ethics: Recent Conceptualizations of Critical Thinking (Volume 1) encapsulates new developments in Critical Thinking skills for MBA students, in the form of a broad-based cross disciplinary primer in business management, with a special focus on business ethics. Each volume encourages critical thinking as a higher order type of thinking that can be taught, leading to a life of rationality, ethics and empathy, which is urgently required of leaders in a global environment where fraud and corruption are rife. Volume 1 explores a working definition of Critical Thinking for this Book; gives the domain, scope and paradigms of Critical Thinking; presents key theories, traditions, schools, models and strategies of Critical Thinking; outlines systems thinking through the lens of Critical Thinking; and, details Critical Thinking for Understanding Basic Fallibility & Falsifiability of Human Thinking. It is essential reading for all MBA students, as well as for researchers and practitioners.